Correlation between success on Standard Progressive Matrices and overall school performance in a sample of Croatian students - Matešić, Krunoslav (2001)
The Standard Progressive Matrices were administered to 2808 primary school students from six schools in Zagreb. The basic statistical parameters were calculated for the entire sample and samples according to age groups from 8 to 9 (N=658) and 9 to 10 (N=2150). The norms are expressed in percentiles. The coefficient of internal reliability Cronbach alpha for the entire sample was 0.93. The correlation between success on the Standard Progressive Matrices and overall school performance was 0.43.
ENG